The Dual Role of Career Women in Providing for the Family: The Perspective of Imam Shafi’i - Musram Doso; Romziatul Widad (STAI Miftahul Ula Nganjuk, 2026)
Changes over time have led to more women working outside the home and taking on dual roles as wives, mothers, and career women. This situation has an impact on family life and harmony. This study aims to examine the dual roles of career women in providing for their families from the perspective of Imam Shafi’i. The study employs a qualitative method using a case study approach through observation, interviews, and literature review. The results indicate that, according to Imam Syafi’i, women are permitted to work to support the family’s economy, particularly when the husband faces financial difficulties, provided that the work is lawful, safe, and does not cause harm. The role of career women can have a positive impact on family well-being, but it also has the potential to cause problems if not balanced with good time management and spousal support. Therefore, cooperation and a balance of roles between husband and wife are essential to maintaining domestic harmony in accordance with Islamic teachings.